The Royal Correspondence of Larsa: I. A Sumerian Prototype for the Prayer of Hezekiah? - Hallo, W. W.
UET 8,70 and dupls., letter of Sin-iddinam to Nin-isina; Ashm. 1932. 520, YBC 4705, YBC 4605, CBS 7072A, UET 6/3, “225”.